ANALISIS KINERJA LAPORAN KEUANGAN SEBAGAI PENGUKUR LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PADA KOPERASI PEGAWAI NEGERI (KPN) PROVINSI KALIMANTAN BARAT - B51107052, THIA IDRIA AMANDA PUTRI (Jurnal KIAFE, 2013)
Civil Servants Cooperative (KPN) is a joint venture entity which is engaged in the economy can not be separated from the use of the funds or money. Mel ihat importance peranakans funds in a business it is necessary to an assessment of financial performance. To assess the performance of an enterprise keuanagan, required stats and proper analysis, so that expenditure of funds or the money will be less than the benefits to be gained. Based on the financial statements in the form of cooperative balance sheet and results of operations or income statement of financial performance conditions can be determined using the ratio Likuidaitas keuanagan covering ratio, Solvabiltas and Profitability. Research conducted at the Civil Servants Cooperative (KPN) in comparison with the Governor's Office Civil Servants Cooperative (KPN) Department of Health and Department of Agriculture, aims to analyze the development of financila and to determine financial performance, when the terms of financial ratios. After research conclusions derived from the results of calculating financial ratios based on balance sheet and results of operations of the period of 2009 s / d 2011 can be said to be under the liquidity ratios Government Servants Cooperative better than Servants Cooperative Health Department and Department of Agriculture, because likuiditasnyatelah exceeding standards normally 125%. However, the solvency ratio State Health Department Cooperative Pegawaai better dibadingkan with Cooperative Civil Service Office of the Governor and the Department of Agriculture, as evidenced by the smaller debt ratio compared to the ratio of smooth. While the ratio profabilitas Government Servants Cooperative and Public Health is better than the Servants Cooperative Plantation Office. Keywords: conclusions derived from the results of calculating financial ratios based on balance sheet and results of operations of the period of 2009 s / d 2011, Liquidity, Solvency, and Profatibilitas.